Camera lens distortion evaluation and correction technique based on a colour CCD moiré method. (November 2018) - Hou, Yue; Zhang, Hongye; Zhao, Jiaye; He, Jian; Qi, Hao; Liu, Zhanwei; Guo, Baoqiao
Highlights: A lens distortion characterization technique was proposed based on a colour CCD moiré method. The mechanism of the colour CCD moiré formation was further studied and explained. The distortion and deformation of two types of lens are characterized and analyzed in detail. Abstract: This study proposes a lens distortion characterization technique based on a colour charge coupled device (CCD) moiré method. The colour CCD imaging lattice unit can be considered as three sets of parallel integrated reference gratings. An image formed from the reflected light of a physical grating through a lens was selected as a specimen grating. High-contrast colour moiré stripes were formed by superimposing the three sets of reference gratings and the specimen grating under specific conditions. The mechanism of colour CCD moiré formation was further studied and illustrated. The specimen grating image is modulated by lens distortion, and thus the formed moiré stripes carry amplified lens distortion information. The principle of lens distortion extraction was described in detail. During moiré image processing, a high-contrast image could be obtained by extracting the blue or red values of the original fringe pattern, which were determined by the distribution of the three colour filter arrays on the filter. Because the ultimate resolution of the camera is fully utilised, this method has a high sensitivity and accuracy in the distortion measurement. It not only very intuitively reflects all features of the lens distortion field, but is also very convenient for obtaining the distortion parameters of the lens distortion field. Finally, the distortion and deformation of two types of lens were characterized and analysed using the colour CCD moiré method.